Zirconium oxide nano structure for realizing structural color as well as preparation method and application of zirconium oxide nano structure
By etching the periodic structure using focusing ion beam technology on the zirconia film, the problem of single structure color and complex preparation in the prior art is solved, and structural colors with wide color gamut, high resolution, high saturation and brightness are achieved in the visible light band.
Patent Information
- Application Number
- CN202411511069.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The prior art has problems such as single color, complex preparation process, poor etch resistance and unstable properties in the field of structural colors. Especially in the visible light band, there is little research, making it difficult to achieve structural colors with wide color gamut, high resolution, high saturation and brightness.
Zirconia photoresist is used to coat the substrate to form a film, and calcinate it in one step to form a zirconia film. Combined with focusing ion beam technology, the periodic structure is etched on the film to achieve structural color.
The wide color gamut, high resolution, high saturation and brightness structure colors in the visible light band are realized, simplifying the preparation process and avoiding the sacrifice of polymer templates and cumbersome peeling process.
Smart Images

Figure HDA0005105488460000011 
Figure HDA0005105488460000012 
Figure HDA0005105488460000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of structural color super surface, and in particular to a zirconium oxide nanostructure for realizing structural color, and a preparation method and application thereof. Background Art
[0002] Color plays a vital role in the world we live in and is the basis for humans to perceive and identify nature in daily life. However, it exhibits limited stability, poor resolution, and environmental pollution, making it unsuitable for emerging display devices that require extremely high resolution. The structural color presented by the special arrangement of the microstructure on the surface of an object is different from the color determined by the chemical composition. It is produced by the reflection and diffraction of light on the microstructure and can be seen everywhere in nature, such as butterfly wings, fish scales, pearls, etc., which all show beautiful and colorful structural colors.
[0003] Plasmonic metal (such as precious metals such as gold or silver) metasurfaces can achieve extremely high-resolution structural coloring beyond the diffraction limit, but the inherent Ohmic loss caused by the free electron response in metal materials affects the color purity and efficiency of the structural color, and its incompatibility with complementary metal oxide semiconductor (CMOS) manufacturing process also limits its application in optical devices.
[0004] All-dielectric resonators have emerged as a potential alternative. All-dielectric metasurfaces are composed of dielectric materials with high refractive index and low loss, such as silicon (YANG W, XIAO S, SONG Q, et al. All-dielectric metasurface for high-performance structural color [J]. Nature Communications, 2020, 11 (1): 1864.), titanium oxide (Sun S, Zhou Z, Zhang C, et al. All-dielectric full-color printing with TiO2 metasurfaces [J]. ACS nano, 2017, 11 (5): 4445-4452.), etc., which can support electric and magnetic field multipole modes based on Mie resonance theory, and are used to achieve high-performance structural colors and improve diffraction-limited resolution. Compared with the inherent ohmic loss of metal materials that limits the color purity and efficiency of plasma structural colors, all-dielectric metasurface materials have the advantages of low loss, high resolution, stability and adjustability, making them better candidates in the field of structural colors.
[0005] However, the high-order Mie resonance of existing all-dielectric materials such as silicon will produce unnecessary sub-peaks, seriously affecting the monochromaticity of the color, reducing efficiency, and is limited to the problems of poor etching resistance, unstable properties and large absorption coefficient of silicon. Zirconia is a high-refractive-index metal oxide material with high refractive index, high transparency, and compatibility with CMOS. It has a high refractive index of 2.0-2.2 in the visible light band and an absorption coefficient close to 0. It can scatter and diffract the incident light through the microstructure, thereby producing a reflection or transmission effect of a specific color. And because zirconium oxide, as an inorganic material, has strong corrosion resistance and wear resistance, it can play a good protective role in the original color and gloss in structural color. For example, Chinese patent document CN104071839A discloses a method for preparing a green zirconium oxide superstructure colorant, wherein a microemulsion method is used to prepare polymethyl methacrylate colloidal spheres with a diameter of 410±10 nm, and a polymethyl methacrylate template with a close-packed face-centered cubic structure is obtained by self-assembly; 6g of zirconium acetate and 6g of methanol are put into a glass bottle and mixed and stirred to obtain a precursor mixture, which is infiltrated into the gap of the template to solidify; then it is placed in a quartz tube furnace and baked in a reducing atmosphere at 450-500°C for 2h, maintaining a heating rate of 2-4°C / min and a nitrogen inflow of 0.6L / min, to obtain a gorgeous single green zirconium oxide superstructure colorant, which has the characteristics of non-toxicity, high saturation, high brightness and never fading, and is an environmentally friendly new colorant. However, the zirconium oxide superstructure colorant prepared by the invention has a single color. In addition, the zirconium oxide superstructure colorant not only has a complicated preparation process, but also requires sacrificial polymer templates and final carbon doping.
[0006] At present, the research on zirconium oxide in the field of structural color is limited to the deep ultraviolet region for holograms (Kim J, Kim W, Oh DK, et al. One-step printable platform for high-efficiency metasurfaces down to the deep-ultraviolet region [J]. Light: Science & Applications, 2023, 12 (1): 68. Kang H, Kim H, Kim K, et al. Printable Spin-Multiplexed Metasurfaces for Ultraviolet Holographic Displays [J]. ACS nano, 2024, 18 (32): 21504-21511.), and there is little research in the visible light band. For the construction of structural color metasurfaces, electron beam evaporation, atomic layer deposition and magnetron sputtering are mostly used to produce thin films, and polymer photoresist is used as a mask. Later, stripping and other processes are required, which makes it limited in practical applications.
[0007] Therefore, it is of great significance to develop a nanostructure with a simple preparation method and structural color that exhibits wide color gamut, high resolution, high saturation and brightness in the visible light band. Summary of the invention
[0008] In view of the shortcomings of the prior art, the present invention provides a zirconium oxide nanostructure for realizing structural color and its preparation method and application. The present invention uses a metal oxide photoresist to coat a substrate to form a film, calcines in one step to form an oxide film, and combines focused ion beam technology to etch a periodic structure on the film to realize structural color; the preparation method of the present invention is simple, and the structural color of the obtained nanostructure in the visible light band shows a wide color gamut, high resolution, high saturation and brightness, and has a wide range of application value.
[0009] The technical solution of the present invention is as follows:
[0010] A method for preparing a zirconium oxide nanostructure for achieving structural color, comprising the steps of:
[0011] (1) coating a zirconium oxide photoresist solution on a substrate surface to form a film, and calcining to obtain an inorganic zirconium oxide thin film;
[0012] (2) A conductive layer is sputtered on the surface of the inorganic zirconium oxide film, and then focused ion beam etching is performed to obtain a zirconium oxide nanostructure.
[0013] According to the preferred embodiment of the present invention, in step (1), the zirconium oxide photoresist is selected from zirconium oxide nanoparticle photoresist with benzoic acid and methacrylic acid as ligands or Zr6O4(OH)4(OMc) 12 One or both of the photoresists, Zr6O4(OH)4(OMc) 12 In photoresist, the group OMc is CH2=CH(CH3)COO - . Zr6O4(OH)4(OMc) 12 The synthesis method of photoresist can be found in the literature “Wang Q, Cui H, Wang X, et al. Exceptional light sensitivity by thiol-ene clicklithography[J]. Journal of the American Chemical Society, 2023, 145(5): 3064-3074.”.
[0014] Preferably, the preparation method of zirconium oxide nanoparticle photoresist with benzoic acid and methacrylic acid as ligands is as follows:
[0015] The n-butanol solution of zirconium n-butoxide or the n-propanol solution of zirconium n-propoxide and tetrahydrofuran are mixed evenly to obtain solution A; benzoic acid, methacrylic acid, triethylamine and tetrahydrofuran are mixed evenly to obtain solution B; solution B and solution A are mixed evenly, reacted, and rotary evaporated to obtain zirconium oxide nanoparticle photoresist with benzoic acid and methacrylic acid as ligands.
[0016] Further preferably, the concentration of the n-butanol solution of zirconium n-butoxide is 80wt%, and the concentration of the n-propanol solution of zirconium n-propoxide is 70wt%; the mass ratio of the n-butanol solution of zirconium n-butoxide or the n-propanol solution of zirconium n-propoxide and tetrahydrofuran is 1-3:1; the molar ratio of benzoic acid, methacrylic acid and triethylamine is 1:1:0.1-0.3, and the mass ratio of benzoic acid and tetrahydrofuran is 1:1-2; the molar ratio of zirconium n-butoxide or zirconium n-propoxide and benzoic acid is 1:1-2; the reaction temperature is 50-60°C, the reaction time is 20-30h, and the reaction is carried out under stirring and reflux conditions.
[0017] Preferably according to the present invention, in step (1), the concentration of the zirconium oxide photoresist solution is 10wt%-80wt%, preferably 60wt%.
[0018] Preferably, according to the present invention, in step (1), the solvent used for the zirconium oxide photoresist solution is selected from one or a combination of two or more of propylene glycol methyl ether acetate (PGMEA), propylene glycol methyl ether (PM), ethyl lactate, butyl lactate, dimethyl sulfoxide or tetrahydrofuran.
[0019] According to the preferred embodiment of the present invention, in step (1), the substrate is silicon dioxide, ITO glass or aluminum oxide. Preferably, the substrate is silicon dioxide.
[0020] Preferably according to the present invention, in step (1), the coating method is spin coating, the spin coating speed is 800-1200 rpm / min, and the spin coating time is 40-80 s.
[0021] Preferably according to the present invention, in step (1), the film forming temperature is 60-100° C., and the film forming time is 5-15 min.
[0022] According to the preferred embodiment of the present invention, in step (1), the calcination temperature is 520-800°C, the calcination time is 2-12 hours, and the calcination atmosphere is air. Preferably, the calcination temperature is 500-600°C.
[0023] Preferably according to the present invention, in step (1), the thickness of the inorganic zirconium oxide film is 0.2-0.5 μm.
[0024] According to the preferred embodiment of the present invention, in step (2), the conductive layer material is one of chromium, gold or ITO; the thickness of the conductive layer is 10nm-60nm, and the sputtering method is magnetron sputtering or ion sputtering.
[0025] Preferably, in step (2), a scanning electron microscope-focused ion beam (SEM-FIB) is used for etching, the etching voltage is 30KV, the etching current is 7.7pA-0.23nA, and the ion beam injection time is 200ns-10.0μs. Preferably, the etching current is 24pA-0.23nA, and the ion beam injection time is 1.0μs.
[0026] Preferably, in step (2), the etching period p is 300nm, 320nm, 350nm, 380nm or 400nm, the width w of the retained line is 150nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm or 260nm; the length of the retained line is greater than 300nm; the number of retained lines is greater than or equal to 2. Preferably, the width w of the retained line is 150nm, 170nm, 180nm, 210nm or 220nm. The retained lines refer to the raised lines left after etching on both sides, and the etching period is the sum of the width of a retained line and the width of an adjacent etched line.
[0027] Preferably according to the present invention, in step (2), the etching depth is 200-600 nm.
[0028] Preferably, according to the present invention, in step (2), the color of the structural color in the visible light band is regulated by regulating the etching current and / or the etching period and / or the width of the retained line and / or the etching depth.
[0029] A zirconium oxide nanostructure for achieving structural color is prepared by the above method.
[0030] The above-mentioned zirconium oxide nanostructure that realizes structural color is used in structural color devices in the visible light band.
[0031] The technical features and beneficial effects of the present invention are as follows:
[0032] 1. The present invention uses zirconium oxide photoresist to coat a substrate to form a film, and calcines in one step to form a zirconium oxide film. The zirconium oxide film of the present invention has high thermal stability and good film quality. In the method for preparing the zirconium oxide film of the present invention, the calcination temperature needs to be appropriate. If it is not appropriate, a zirconium oxide film with a high refractive index cannot be obtained, thereby affecting the structural color performance of the zirconium oxide nanostructure.
[0033] 2. Etching is performed on the zirconium oxide film according to the designed periodic pattern, that is, cyclic etching of retaining lines-etching lines-retaining lines-etching lines is performed according to the period to achieve a periodic arrangement of the retained lines. The zirconium oxide nanostructure etched by the present invention using focused ion beam technology has coordination and high precision, can achieve high-precision imaging, and has application feasibility; and the preparation method is simple, avoiding the sacrifice of the polymer template and cumbersome post-processing processes such as peeling. The present invention achieves the regulation of structural color in the visible light band by regulating the etching current and / or the etching cycle and / or the width of the retained lines and / or the etching depth, and achieves the regulation of structural colors in a wide color range of blue, green, orange, red, purple, etc.
[0034] 3. The nanostructure of the present invention can achieve structural color with a small number of retained lines (as few as 2) and a length of retained lines (as small as more than 300 nanometers), indicating that the structural color of the nanostructure of the present invention in the visible light band has high resolution. At the same time, the structural color of the zirconium oxide nanostructure of the present invention in the visible light band exhibits a wide color gamut, high saturation and brightness, and the color gamut area is close to sRGB, which is suitable for reflection, transmission and polarization modes, and has a wide range of application value.
[0035] 4. In the present invention, a small etching current will obtain a periodic zirconia grating with high precision, and a structural color with a wide color gamut can be obtained, while a large etching current will reduce the color gamut of the structural color. In addition, the etching depth will affect the actual etching line width, and then affect the periodic arrangement of the zirconia grating, causing the displayed color to shift. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1This is the thermogravimetric spectrum of ZrO2-MAA / BA obtained in Example 1 under nitrogen and air environments.
[0037] Figure 2 This is the particle size analysis spectrum of ZrO2-MAA / BA obtained in Example 1.
[0038] Figure 3 The morphology of the photoresist film (a) and the zirconium oxide film (b) obtained in Example 1 under an atomic force microscope.
[0039] Figure 4 This is a graph showing the relationship between the film thickness of the photoresist film obtained by the method of Example 1 and the calcination temperature after calcination for 2 hours at different temperatures.
[0040] Figure 5 This is a relationship diagram between the refractive index n and the calcination temperature of the photoresist film obtained by the method of Example 1 calcined at different temperatures for 2 hours, and the wavelength range is 400-800nm.
[0041] Figure 6 1 is a scanning electron microscope image of the zirconium oxide nanostructures prepared in Examples 1-15 and the corresponding experimental structural colors in the reflective orthogonal polarization mode of a polarizing microscope.
[0042] Figure 7 1 and 2 are scanning electron microscope images of the zirconium oxide nanostructures prepared in Examples 16-25 and the corresponding experimental structural colors in the reflective orthogonal polarization mode of a polarizing microscope.
[0043] Figure 8 3 is a graph showing the relationship between the actual line width and etching depth in Experimental Example 4.
[0044] Fig. 9 : is the chromaticity diagram (CIE 1931) of the experimental structural color of the zirconium oxide nanostructure in Experimental Example 5. The etching depth is 400 nm, and the triangle is the standard sRGB color gamut. DETAILED DESCRIPTION
[0045] The present invention is further described below by specific examples, and the raw materials in the examples are all commercially available. It should be understood that the following examples are only for illustrative purposes and explanation of the present invention, and do not limit the scope of protection of the present invention.
[0046] Example 1
[0047] A method for preparing a zirconium oxide nanostructure for achieving structural color, comprising the steps of:
[0048] (1) 10.0 g of 80 wt% zirconium n-butoxide (0.021 mol) in n-butanol solution and 5 g of tetrahydrofuran were mixed to form solution A; 3.91 g of benzoic acid (0.032 mol), 2.75 g of methacrylic acid (0.032 mol), 0.71 g of triethylamine (0.007 mol), and 5 g of tetrahydrofuran were mixed to form solution B; solution B and solution A were mixed to form solution B; the reflux temperature was set to 60°C and the reflux time was set to 24 h in an oil bath, and the reaction was stirred. After the reaction was completed, the temperature naturally dropped to room temperature, and then the solvent was removed by rotary evaporation at 50°C-55°C for 30 min to obtain a white transparent liquid, which was named ZrO2-MAA / BA.
[0049] Thermal analysis of the product ZrO2-MAA / BA was performed. Thermal analysis (NETZSCH, model STA449F3): In a nitrogen or air environment, the temperature was increased at a rate of 10°C / min from 25°C to 800°C. The obtained thermal analysis curve is as follows Figure 1 As shown in the figure, it can be seen that the ZrO2-MAA / BA material contains 26.4wt% of inorganic zirconium oxide component.
[0050] The product ZrO2-MAA / BA was subjected to particle size analysis. Dynamic light scattering instrument (Anton Paar, model: Litesizer 500): PGMEA was used as solvent to prepare ZrO2-MAA / BA with a concentration of 15 wt%. The obtained particle size distribution curve is shown in Figure 2 As shown in the figure, it can be seen that the average particle size of ZrO2-MAA / BA is small and evenly distributed.
[0051] (2) Preparation of zirconium oxide film: dissolve the product ZrO2-MAA / BA in PGMEA, the mass ratio of ZrO2-MAA / BA to PGMEA is 3:2, and filter with a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm to obtain a photoresist solution. 2 The quartz sheet was adsorbed on the spin coater, and the coating was spun at 1000 rpm / min for 60 seconds, and then baked on a hot plate at 80°C for 10 minutes to obtain a photoresist film. Then it was placed in a muffle furnace and kept at 600°C for 2 hours in an air atmosphere, with a heating rate of 10°C min -1 , further remove organic matter to obtain an inorganic zirconium oxide film with a thickness of 0.3μm.
[0052] The surface morphology of the unfired photoresist film after spin coating and the film calcined at 600°C for 2h were collected using an atomic force microscope (AFM) (Germany, model: Bruker Dimension Icon) in light touch mode. The collection area was set to 3μm*3μm. The surface morphology of the photoresist film and the zirconium oxide film are shown in Figure 2. Figure 3As shown in a and b, the root mean square roughness (Rq) is 0.23nm and 0.18nm, respectively, indicating that the surface of the zirconia film is flat and smooth.
[0053] (3) A 60 nm thick chromium layer was magnetron sputtered on the surface of the inorganic zirconia film using a chromium target. According to the design drawing, a scanning electron microscope-focused ion beam (SEM-FIB) (USA, model: Helios 5CX, Thermo Fisher Scientific) was used to etch the zirconia film. The basic conditions were: etching voltage of 30 kV, etching current of 24 pA, ion beam injection time of 1.0 μs, etching period p of 300 nm, width w of the retained line of 150 nm (referred to as p300w150), length of the retained line of 3 μm, number of retained lines of 9, etching depth of 400 nm, wherein the retained lines refer to the raised lines left on both sides after etching, and the etching period is the sum of the width of a retained line and the width of an adjacent etched line, thereby obtaining a zirconia nanostructure.
[0054] Example 2
[0055] A method for preparing a zirconium oxide nanostructure that achieves structural color is as described in Example 1, except that in step (3), the etching current is 80 pA; the other steps and conditions are the same as in Example 1.
[0056] Example 3
[0057] A method for preparing a zirconium oxide nanostructure that achieves structural color is as described in Example 1, except that in step (3), the etching current is 0.23 nA; the other steps and conditions are the same as in Example 1.
[0058] Example 4
[0059] A method for preparing a zirconium oxide nanostructure to achieve structural color is as described in Example 1, except that in step (3), the etching period p is 320nm and the width w of the retained line is 170nm (abbreviated as p320w170); the other steps and conditions are the same as in Example 1.
[0060] Example 5
[0061] A method for preparing a zirconium oxide nanostructure that achieves structural color is as described in Example 4, except that in step (3), the etching current is 80 pA; the other steps and conditions are the same as in Example 1.
[0062] Example 6
[0063] A method for preparing a zirconium oxide nanostructure that achieves structural color is as described in Example 4, except that in step (3), the etching current is 0.23 nA; the other steps and conditions are the same as in Example 1.
[0064] Example 7
[0065] A method for preparing a zirconium oxide nanostructure to achieve structural color is as described in Example 1, except that in step (3), the etching period p is 350nm and the width w of the retained line is 180nm (abbreviated as p350w180); the other steps and conditions are the same as in Example 1.
[0066] Example 8
[0067] A method for preparing a zirconium oxide nanostructure that achieves structural color is as described in Example 7, except that in step (3), the etching current is 80 pA; the other steps and conditions are the same as in Example 1.
[0068] Example 9
[0069] A method for preparing a zirconium oxide nanostructure that achieves structural color is as described in Example 7, except that in step (3), the etching current is 0.23 nA; the other steps and conditions are the same as in Example 1.
[0070] Example 10
[0071] A method for preparing a zirconium oxide nanostructure to achieve structural color is as described in Example 1, except that in step (3), the etching period p is 380nm and the width w of the retained line is 210nm (abbreviated as p380w210); the other steps and conditions are the same as in Example 1.
[0072] Embodiment 11
[0073] A method for preparing a zirconium oxide nanostructure that achieves structural color is as described in Example 10, except that in step (3), the etching current is 80 pA; the other steps and conditions are the same as in Example 1.
[0074] Example 12
[0075] A method for preparing a zirconium oxide nanostructure that achieves structural color is as described in Example 10, except that in step (3), the etching current is 0.23 nA; the other steps and conditions are the same as in Example 1.
[0076] Embodiment 13
[0077] A method for preparing a zirconium oxide nanostructure to achieve structural color is as described in Example 1, except that in step (3), the etching period p is 400nm and the width w of the retained line is 220nm (abbreviated as p400w220); the other steps and conditions are the same as in Example 1.
[0078] Embodiment 14
[0079] A method for preparing a zirconium oxide nanostructure that achieves structural color is as described in Example 13, except that in step (3), the etching current is 80pA; the other steps and conditions are the same as in Example 1.
[0080] Embodiment 15
[0081] A method for preparing a zirconium oxide nanostructure that achieves structural color is as described in Example 13, except that in step (3), the etching current is 0.23 nA; the other steps and conditions are the same as in Example 1.
[0082] Example 16
[0083] A method for preparing a zirconium oxide nanostructure to achieve structural color is as described in Example 1, except that in step (3), the etching depth is 600 nm; the other steps and conditions are the same as in Example 1.
[0084] Embodiment 17
[0085] A method for preparing a zirconium oxide nanostructure to achieve structural color is as described in Example 1, except that in step (3), the etching depth is 500 nm; the other steps and conditions are the same as in Example 1.
[0086] Embodiment 18
[0087] A method for preparing a zirconium oxide nanostructure to achieve structural color is as described in Example 4, except that in step (3), the etching depth is 600 nm; the other steps and conditions are the same as in Example 1.
[0088] Embodiment 19
[0089] A method for preparing a zirconium oxide nanostructure to achieve structural color is as described in Example 4, except that in step (3), the etching depth is 500 nm; the other steps and conditions are the same as in Example 1.
[0090] Embodiment 20
[0091] A method for preparing a zirconium oxide nanostructure to achieve structural color is as described in Example 7, except that in step (3), the etching depth is 600 nm; the other steps and conditions are the same as in Example 1.
[0092] Embodiment 21
[0093] A method for preparing a zirconium oxide nanostructure to achieve structural color is as described in Example 7, except that in step (3), the etching depth is 500 nm; the other steps and conditions are the same as in Example 1.
[0094] Embodiment 22
[0095] A method for preparing a zirconium oxide nanostructure to achieve structural color is as described in Example 10, except that in step (3), the etching depth is 600 nm; the other steps and conditions are the same as in Example 1.
[0096] Embodiment 23
[0097] A method for preparing a zirconium oxide nanostructure to achieve structural color is as described in Example 10, except that in step (3), the etching depth is 500 nm; the other steps and conditions are the same as in Example 1.
[0098] Embodiment 24
[0099] A method for preparing a zirconium oxide nanostructure to achieve structural color is as described in Example 13, except that in step (3), the etching depth is 600 nm; the other steps and conditions are the same as in Example 1.
[0100] Embodiment 25
[0101] A method for preparing a zirconium oxide nanostructure to achieve structural color is as described in Example 13, except that in step (3), the etching depth is 500 nm; the other steps and conditions are the same as in Example 1.
[0102] Test Example 1
[0103] The photoresist film prepared by the method of step (2) of Example 1 was calcined in air atmosphere at 100°C, 200°C, 300°C, 400°C, 500°C, and 600°C for 2 h, respectively, with a heating rate of 10°C min -1 .
[0104] The relationship between the film thickness and the calcination temperature was analyzed using an ellipsometer (USA, model: M-2000v) in the wavelength range of 400 to 800 nm. Figure 4 As shown, as the calcination temperature gradually increases, the thickness of the film gradually decreases. The thickness of the film before calcination is 1.8 μm, and the thickness of the film after calcination at 600°C is 0.3 μm.
[0105] The relationship between the refractive index of the film and the calcination temperature was analyzed in the wavelength range of 400 to 800 nm using an ellipsometer (USA, model: M-2000v). Figure 5The results show that with the increase of calcination temperature, the organic components are gradually removed, and the refractive index of the zirconium oxide film gradually increases. After calcination at 600℃ for 2h, the refractive index of the film can reach above 2.0 at a wavelength of 400nm. The film has the characteristics of high refractive index, which is conducive to the realization of structural color.
[0106] Test Example 2
[0107] The etched patterns of the zirconium oxide nanostructures prepared in Examples 1-15 were characterized using the scanning electron microscope imaging function of a scanning electron microscope-focused ion beam (SEM-FIB) system, and the structural colors were obtained using a polarizing microscope (Germany, model: AxioScope AI, ZEISS) in the reflection orthogonal polarization mode, such as Figure 6 As shown, the etched pattern can show blue, dark green, light green, orange, and red structural colors, proving that the zirconium oxide nanostructure has good structural color performance. The etching accuracy is highest when the etching current is 24pA.
[0108] Test Example 3
[0109] The etched patterns of the zirconium oxide nanostructures prepared in Examples 16-25 were characterized using the scanning electron microscope imaging function of a scanning electron microscope-focused ion beam (SEM-FIB) system, and the structural colors were obtained using a polarizing microscope (Germany, model: AxioScope AI, ZEISS) in the reflection orthogonal polarization mode, such as Figure 7 As shown, the overall structural colors are purple, blue, green, orange, and red.
[0110] Test Example 4
[0111] According to the zirconium oxide nanostructures obtained in Example 1 to Example 25, the relationship between the actual line width of etching and the etching depth is obtained, as shown in FIG. Figure 8 As shown, the results show that as the etching depth increases, the actual line width will gradually shorten, and different structural color presentations can be obtained by controlling the etching depth.
[0112] Test Example 5
[0113] According to the zirconium oxide nanostructure obtained in the embodiment, the structural colors obtained at etching current of 24 pA and etching depths of 400 nm, 500 nm, and 600 nm are plotted on a chromaticity diagram (CIE 1931), as shown in FIG. Fig. 9 As shown, the results show that the color gamut area of the experimental structural color of zirconia nanostructure is close to sRGB, proving that zirconia nanostructure has good structural color ability in the visible light band.
Claims
1. A method for preparing a zirconium oxide nanostructure for achieving structural color, comprising the steps of: (1) coating a zirconium oxide photoresist solution on a substrate surface to form a film, and calcining to obtain an inorganic zirconium oxide thin film; (2) A conductive layer is sputtered on the surface of the inorganic zirconium oxide film, and then focused ion beam etching is performed to obtain a zirconium oxide nanostructure.
2. The method for preparing a zirconium oxide nanostructure for achieving structural color according to claim 1, characterized in that: In step (1), the zirconium oxide photoresist is selected from zirconium oxide nanoparticle photoresist with benzoic acid and methacrylic acid as ligands or Zr6O4(OH)4(OMc) 12 One or both of the photoresists, Zr6O4(OH)4(OMc) 12 In photoresist, the group OMc is CH2=CH(CH3)COO - .
3. The method for preparing a zirconium oxide nanostructure for achieving structural color according to claim 2, characterized in that: The preparation method of zirconium oxide nanoparticle photoresist with benzoic acid and methacrylic acid as ligands is as follows: The n-butanol solution of zirconium n-butoxide or the n-propanol solution of zirconium n-propoxide and tetrahydrofuran are mixed evenly to obtain solution A; benzoic acid, methacrylic acid, triethylamine and tetrahydrofuran are mixed evenly to obtain solution B; solution B and solution A are mixed evenly, reacted, and rotary evaporated to obtain zirconium oxide nanoparticle photoresist with benzoic acid and methacrylic acid as ligands; Preferably, the concentration of the n-butanol solution of zirconium n-butoxide is 80 wt %, and the concentration of the n-propanol solution of zirconium n-propoxide is 70 wt %; The mass ratio of the n-butanol solution of zirconium n-butoxide or the n-propanol solution of zirconium n-propoxide to tetrahydrofuran is 1-3:1; the molar ratio of benzoic acid, methacrylic acid and triethylamine is 1:1:0.1-0.3, and the mass ratio of benzoic acid to tetrahydrofuran is 1:1-2; the molar ratio of zirconium n-butoxide or zirconium n-propoxide to benzoic acid is 1:1-2; the reaction temperature is 50-60°C, the reaction time is 20-30h, and the reaction is carried out under stirring and reflux conditions.
4. The method for preparing a zirconium oxide nanostructure for achieving structural color according to claim 1, characterized in that: In step (1), one or more of the following conditions are included: i. The concentration of the zirconium oxide photoresist solution is 10wt%-80wt%, preferably 60wt%; ii. The solvent used in the zirconium oxide photoresist solution is selected from one or a combination of two or more of propylene glycol methyl ether acetate (PGMEA), propylene glycol methyl ether (PM), ethyl lactate, butyl lactate, dimethyl sulfoxide or tetrahydrofuran; iii. The substrate is silicon dioxide, ITO glass or aluminum oxide; preferably, the substrate is silicon dioxide; iv. The coating method is spin coating, the spin coating speed is 800-1200 rpm / min, and the spin coating time is 40-80 s; v. Film forming temperature is 60-100℃, and film forming time is 5-15min; vi. The calcination temperature is 520-800°C, the calcination time is 2-12h, and the calcination atmosphere is air; preferably, the calcination temperature is 500-600°C; vii. The thickness of the inorganic zirconium oxide film is 0.2-0.5 μm.
5. The method for preparing a zirconium oxide nanostructure for achieving structural color according to claim 1, characterized in that: In step (2), the conductive layer material is one of chromium, gold or ITO; the thickness of the conductive layer is 10nm-60nm.
6. The method for preparing a zirconium oxide nanostructure for achieving structural color according to claim 1, characterized in that: In step (2), a scanning electron microscope-focused ion beam (SEM-FIB) is used for etching, the etching voltage is 30KV, the etching current is 7.7pA-0.23nA, and the ion beam injection time is 200ns-10.0μs; preferably, the etching current is 24pA-0.23nA, and the ion beam injection time is 1.0μs.
7. The method for preparing a zirconium oxide nanostructure for achieving structural color according to claim 1, characterized in that: In step (2), the etching period p is 300nm, 320nm, 350nm, 380nm or 400nm, the width w of the retained line is 150nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm or 260nm; the length of the retained line is greater than 300nm; the number of retained lines is greater than or equal to 2; preferably, the width w of the retained line is 150nm, 170nm, 180nm, 210nm or 220nm; Preferably, the etching depth is 200-600 nm.
8. The method for preparing a zirconium oxide nanostructure for achieving structural color according to claim 1, characterized in that: In step (2), the color of the structural color in the visible light band is regulated by regulating the etching current and / or the etching period and / or the width of the retained line and / or the etching depth.
9. A zirconium oxide nanostructure that realizes structural color, prepared by the method according to any one of claims 1 to 8.
10. Application of the zirconium oxide nanostructure that realizes structural color as claimed in claim 9 in a structural color device in the visible light band.
Citation Information
Patent Citations
Preparation method of green zirconium oxide superstructure toner
CN104071839A
Method for manufacturing a structural color filter
CN112198580A
Nanostructure for realizing structural color and preparation method thereof
CN114671402A
Two-dimensional material nanostructure and preparation method and application thereof
CN114955985A
Metastructure surface for realizing structural color based on quasi-continuous domain bound state and preparation method
CN117471577A